Use of a Specific Phage Cocktail for Soft Rot Control on Ware Potatoes: A Case Study - Eugenia N. Bugaeva; Maya V. Voronina; Dmitry M. Vasiliev; Anna A. Lukianova; Nikolay N. Landyshev; Alexander N. Ignatov; Konstantin A. Miroshnikov (Viruses, 2021)
Using bacteriophages (bacterial viruses) to control pathogenic bacteria is a promising approach in horticulture. However, the application of this strategy in real conditions requires compliance with particular technological and environmental restraints. The presented paper concerns the process of phage selection to create a cocktail that is efficient against the circulating causal agents of potato soft rot. The resulting phage cocktail causes a complete lysis of a mixture of circulating pectobacterial strains in vitro. In the context of being used to treat ware potatoes during off-season storage, the protocol of phage application via the humidity maintenance system was designed. The phage cocktail was shown to reduce the population of Pectobacterium spp. 10–12-fold, achieving a population that was below a symptomatic threshold.